Preliminary Optical, Thermal and Structural Design of a 100 kWth CSPonD Beam-down On-sun Demonstration Plant. (August 2015) - Grange, Benjamin; Kumar, Vikas; Gil, Antoni; Armstrong, Peter R.; Codd, Daniel S.; Slocum, Alexander; Calvet, Nicolas
Abstract: An innovative concept in which a single-tank molten salt thermal energy storage arrangement also acts as a volumetric receiver is being developed in connection with the CSPonD 2 (Concentrated Solar Power on Demand Demonstration) project. The tank is located at the focal point of a beam-down tower to act as both solar energy receiver and thermal energy storage. The relatively small angle subtended by rays emanating from the central reflector of a beam down optical system, together with the nature of solar energy absorption within the volumetric receiver, make use of a compound parabolic concentrator (CPC) or CPC-like final optical element attractive. An effective concentration of about 4 can be achieved to increase solar flux at the tank aperture from 150 to 600 suns. This paper describes preliminary designs of the CPC and tank/receiver. Optical simulations reveal that, for a given solar incident power at the tank aperture, a conical final concentrator design produces a more uniform flux distribution with better axial alignment (lower average horizontal component) of rays at its outlet compared to a conventional CPC of revolution. However the cone may require a larger outlet radius, leading to higher thermal losses through the tank aperture. With the current design of the tank, the losses through the walls correspond to 5.5% of the thermal capacity. To maximize the tank thermal efficiency, a thorough investigation will be carried out, starting with measurements of the molten salt emissivity, to determine the cone outlet radius/tank aperture and cone height that achieve maximum system efficiency with a 250-550 °C molten salt working temperature range.